Augmented Reality Navigation System on Android - Chee Oh Chung; Yilun He; Hoe Kyung Jung (International Journal of Electrical and Computer Engineering (IJECE), 2016)
With the advent of the Android system, smart phones are rapidly developing and through the conveniency of accessing internet on the smart phones, a user’s location information can be accessed anywhere and anytime easily. Augmented Reality Based Technology enables the provision of variety information such as pictures and location of buildings in the navigation field. Most of the augmented reality program used to Visual Trace Method (Marker method and Markerless Method). For the Visual Trace Method, the marker installation and digital information should be assigned while the Non-visual Trace Method requires the use of hardware (G.P.S, sensors etc). Most navigation systems can only show the path from a user’s current location to their destination. In this paper, the design and implementation of an augmented reality program is discussed. It will use the smart phone’s inbuilt camera and GPS to display a user’s surround information in real time on the smart phone. The proposed system will combine the G.P.S location-based technology and virtual trace technology to provide the user with basic information about a building they are looking for or one in their immediate surrounding.